Peningkatan Kemampuan Mengenal Konsep Bilangan 1 - 10 Menggunakan Media Audio Visual Bagi Anak Tunagrahita ringan (Classroom Action Research Kelas II Di SLB Negeri 037702 sidikalang) - Saragiih, Lourina Lasmariah; Utami, Iga Setia (Jurnal Penelitian Pendidikan Khusus, 2022)
This study describes the improvement in ability to recognize the number 1-10 concepts using audiovisual media in class IV children with mild intellectual disability from SLB Negeri 037702 Sidikalang. This research is motivated by the problems faced by teachers who do not teach mathematics well. This affects student learning outcomes. B. When students do not understand the concept of numbers. This study aims to improve the ability to recognize the number 1-10 concept through audiovisual media in class II children with mild intellectual disability from SDLB Negeri 037702 Sidikalang. The type of study used is classroom action research (CAR). Data were collected through observation, testing, documentation, and processed qualitatively and quantitatively. The research was conducted in collaboration with the class teacher, and behavioral activities were conducted in her two cycles. Each cycle consists of four of her 60 minute sessions. The results of a study conducted show that audiovisual media can improve the ability to recognize the concept of numbers in class II mildly mentally handicapped children of SLB Negeri 037702 Sidikalang, showing that the student's score is higher than that of his KKM class. higher than the score of , is proof. that the research objectives have been achieved.